Effects of osmopriming on tomato (Lycopersicon esculentum M.) hybrid seed vigor under aging and salinity stress - Dan, Chiang Lin; Ling, Yao Bai; Xun, Qian Lu (Global Journal of Food and Agribusiness Management, 2017)
This study investigates the effects of osmopriming on tomato (Lycopersicon esculentum M.) hybrid seed vigor under aging and salinity stress. Tomato seeds of the ZZ1 hybrid variety, stored for four years under natural (aged) or -20°C (unaged) conditions were primed in 10% (w/v) polyethylene glycol (PEG) solution for 2 d at 20±1°C in the dark. The seed vigor was evaluated at 25±1°C for 7 d under normal (water) and 100 mM NaCl conditions, respectively. Results show that the germination percentage (GP), germination index (GI) and mean germination rate (MGR) of primed, aged seeds were significantly enhanced with a substantial increase in the radicle length (RL), shoot length (SL) and total fresh weight (FW) compared with unprimed aged seeds. Similarly, the GI, MGR and FW significantly increased in primed seeds compared with unprimed seeds under salinity stress, while GP, RL and SL did not show significant differences. Furthermore, a decline in the relative electrolyte leakage (REL) and in malondialdehyde (MDA) was detected in primed seeds during the imbibition stage compared with unprimed seeds under aging and salinity stress. The negative correlations between seed vigor and REL and MDA were observed which suggests that seed priming improves seed vigor under stress conditions associated with a decrease in seed lipid peroxidation.